The Role of Administrative Communication in Crisis Management from the point of view of employees in the Public Relations Department of the Ministry of Interior in the Kingdom of Saudi Arabia - Al- Maamari, Jamal Abdullah (Journal of Humanities & Social Sciences, 2021)
The current research aimed to identify the importance of communication in crisis management From the point of view of employees in the Public Relations Department of the Ministry of Interior in the Kingdom of Saudi Arabia, and the role of communication during the stages of the crisis. The research used the descriptive approach and the questionnaire as a research tool that was distributed to the research sample (63), and the (SPSS). The results showed that the role of communication for crisis management in the Ministry of Interior was very high, with a mean (4.29) and The role of using communication in crisis management was very high, with an average (4.35), Communication contributes to finding an efficient system that provides accurate data and information on the extent of the crisis. The researcher recommended activating effective means and methods of communication between workers and management in the Ministry of Interior